Las prácticas lean y su aporte a la disminución de impactos ambientales del sector de la construcción - Bahamón-Jaramillo, Sara; Botero, Luis Fernando Botero; Vásquez-Hernández, Alejandro (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Lean and Sustainable Construction are two philosophies that share the purpose of efficient use of resources. However, they are mostly applied individually without considering the integration of both in a Construction project. This study seeks to identify the environmental impacts of the most usual Construction activities and Lean Construction practices that help reduce, mitigate or prevent them. For this, an interaction matrix was developed to identify the environmental impacts associated with each Construction activity considered and subsequently, a detailed literature review was carried out looking for Lean practices that could contribute to the prevention or reduction of these impacts. The generation of ordinary, recyclable, hazardous and C&D wastes are the environmental impacts with the greatest number of Lean Construction practices that can help reduce or prevent them. Of the 13 Lean Construction practices identified, prefabricated Construction is the practice that may contribute to the reduction or prevention of the majority of the environmental impacts (12 of them).